Keynote Speaker Invitation, 24 November 2012 - Norsiah, Fauzan (Universiti Malaysia Sarawak, 2012)
To present paper as a keynote speaker on the UPI CIBIRU International Seminar, to be held on November 24, 2012, at auditorium FPMIPA, JICA Building, Universitas Pendidikan Indonesia, Jalan Dr. Setiabudhi No. 229 Bandung, Indonesia.